English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

x / (x-2) + 1 / (x+1) = 2 / (x-2)
* multiply with LCD which is (x-2)(x+1)

[ x / (x-2) + 1 / (x+1) = 2 / (x-2)]
x (x+1) + (x-2) = 2 (x+1)
x^2 + x + x - 2 = 2x +2
x^2 + 2x - 2x = 2 + 2
x^2 = 4
x = +/-2

ANSWER = 2 and -2

2007-01-21 12:34:45 · answer #1 · answered by swas77 2 · 0 0

Start by multiplying both sides by (x-2)(x+1) to clear the denominators. This will give

x(x+1) + (x-2) = 2(x+1)

expand this equation

x^2 + x + x - 2 = 2x + 2

and then move it around to get a 2nd order polynomial to factor and solve

x^2 - 4 = 0

I will let you take it from there.

2007-01-21 20:33:01 · answer #2 · answered by rscanner 6 · 0 0

(1/x+1)=(2-x/x-2)
(1/x+1)=-(x-2/x-2)=-1
-1/x+1=1
1=x+1
x=0

2007-01-21 20:31:32 · answer #3 · answered by VanessaM 3 · 0 1

fedest.com, questions and answers